Controlling the Menace of Cartelization in Pakistan: Criminalization is a Way Forward - Attia Madni (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The criminal penalties for cartels have helped many jurisdictions around the globe to make rigorous detections into anti-trust violations controlling this menace effectively. The criminal punishments have certain admitted benefits over the civil fines for such violations. The deterrence achieved through criminal sanctions enables the leniency/amnesty programs run successfully. This study, through qualitative content analysis, aims at describing the significance of criminalizing cartels in Pakistan with an overview of the ineffectiveness of existing anti-cartel law in the country. It encompasses the core advantages of adding parallel liabilities i.e. criminal penalties along with civil liabilities for better detection of cartels and the subsequent punishments of all concerned. The writers have described the tools for curbing anti-trust violations through adding parallel liabilities for them in the country. The research concludes that the existing anti-cartel regime (based on civil remedies) in Pakistan is inadequate to curb it down and it is high time to criminalizing cartels in Pakistan. Holding the cartelists criminally liable along with effectuating recovery of fines with effective use of leniency program and settlement procedures is the only way forward for Pakistan.